PEMBELAJARAN PROBLEM PASING STRATEGIS CARD SORT UNTUK MENINGKATKAN MINAT DAN HASIL RAB KELAS XII DPIB SMK NEGERI 1 CALANG - DEWI RINA MOULIANA (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
The results showed that from the results of the questionnaire regarding students' interest in learning, there was an increase in learning interest from cycle I to cycle II. This can be seen from the student's interest in learning in the first cycle there are 1 student (2.85%) for the high interest criteria there are 25 students (71.42%) for the moderate interest criteria, while in the second cycle there are 31 students (88.57%) with high interest criteria, based on the assessment criteria, namely 76% - 100% said to be of high interest. While the results of the tests carried out, there was an increase in student learning outcomes, from 35 students only 25 students (71.42%) who finished studying in the first cycle to 33 students (94.28%) in the second cycle. This shows that the second cycle has reached the classical KKM standard, which is 70% of students must get a score of 70. And there is a significant difference between cycle I and cycle II with the obtained value of tcount 10,8 > ttable 2,0322. Based on the above analysis, it can be concluded that the application of the Problem Posing learning model with the Card Sort learning strategy can increase students' interest and learning outcomes in the Budget Plan for the competency standard to understand the project management cycle in class XI of Building Drawing Engineering at SMKN.1 Calang in the 2021/2022 academic year. ABSTRAKHasil penelitian menunjukkan bahwa dari hasil angket mengenai minat belajar siswa menunjukkan adanya peningkatan minat belajar dari siklus I ke siklus II. Hal ini terlihat dari minat belajar siswa pada siklus I terdapat 1 siswa (2,85%) untuk kriteria minat tinggi ada 25 siswa (71,42%) untuk kriteria minat sedang , sedangkan pada siklus II terdapat 31 siswa (88,57%) dengan kriteria minat tinggi, berdasarkan kriteria penilaian yaitu 76% - 100% dikatakan minat tinggi. Sedangkan hasiltes yang dilaksanakan, terdapat peningkatan hasil belajar siswa yaitu dari 35 siswa hanya 25 siswa (71,42%) yang tuntas belajar pada siklus I menjadi 33 siswa (94,28%) pada siklus II. Hal ini menunjukan siklus II sudah mencapai standar KKM secara klasikal yaitu 70% siswa harus memperoleh nilai ? 70. Dan adanya perbedaan yang signifikan antara siklus I dan siklus II dengan diperoleh nilai thitung10,8 > ttabel 2,0322. Berdasarkan analisis diatas dapat disimpulkan bahwa penerapan Model pembelajaran Problem Posing dengan strategi pembelajaran Card Sort dapat meningkatkan minat dan hasil belajar Rencana Anggaran Biaya siswa pada standar kompetensi memahami siklus managemant proyek di kelas XI Teknik Gambar Bangunan SMKN.1 Calang Tahun Pembelajaran 2021/2022.